1999
DOI: 10.1017/s1047951100008398
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical screening of neonates for congenital heart defects: the cases we miss

Abstract: In a population-based study of 35,218 infants born alive during the 15 years from 1982 to 1996, 353 (1%) were diagnosed as having a congenital heart defect, of whom 84 (24%) were diagnosed subsequent to discharge from hospital after birth (2.4/1000). Of these, 40 (48%) had a ventricular septal defect, 14 (17%) an atrial septal defect, 9 (11%) a patent arterial duct, 8 (10%) an aortic stenosis and 13 (15%) other defects. Compared with those in whom diagnosis was made before discharge, the group of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 17 publications
(6 reference statements)
8
38
1
3
Order By: Relevance
“…In a much smaller study from a hospital with only 2300 births a year Meberg et al reported a lower rate of late diagnosis 14. They also found that coarctation of the aorta and aortic valve stenosis were the potentially dangerous malformations most likely to be overlooked before discharge.…”
Section: Discussionmentioning
confidence: 97%
“…In a much smaller study from a hospital with only 2300 births a year Meberg et al reported a lower rate of late diagnosis 14. They also found that coarctation of the aorta and aortic valve stenosis were the potentially dangerous malformations most likely to be overlooked before discharge.…”
Section: Discussionmentioning
confidence: 97%
“…For years, published reports have addressed this issue aiming at increasing the neonatologists or paediatricians awareness of the suspicious clinical ®ndings and of the possible pitfalls in the clinical diagnosis of heart defects [5]; and yet, over the years, ®gures of the proportion of newborns and infants with their cardiac disease missed in early life have not really changed [7]. In 1986, it was reported that 32% of infants admitted to one centre for the presence of major congenital heart defects had initially been discharged home from the birth clinic [5].…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, it was reported that 32% of infants admitted to one centre for the presence of major congenital heart defects had initially been discharged home from the birth clinic [5]. Two very recent populationbased studies again showed a high proportion of infants with heart defects not diagnosed early in life: in one report 24% of all children diagnosed as having congenital heart disease had initially been sent home as healthy from the birth clinic [7] and in another study it was observed that a substantial proportion of infants with initially undiagnosed cardiac malformations had an adverse outcome with 10% of all infants dying because of heart defects doing so with only post-mortem diagnosis of the cardiac anomaly [6]. A previous study even found a proportion as high as 30% of all infants dying from congenital heart disease not having been diagnosed until after death [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben dem optimalen Zeitpunkt des POS werden in der Literatur der Grenzwert, bestimmte Anforderungen an die verwendeten Geräte und die Sinnhaftigkeit vergleichender Messungen an oberen und unteren Extremitäten diskutiert [6,11,15,17,19,30]. Der in unserer Studie verwendete Grenzwert (Normalbefund ≥96%) stimmt mit dem von Koppel et al [13] angegebenen überein.…”
Section: Diskussionunclassified